A genre analysis of Islamic academic research article introductions - Ahamad Shah, Mohamed Ismail; Mohd Yusof, Amira (Elsevier, 2012)
This study explores the rhetorical organization of Islamic research article introductions based on Swales’ (1990) CARS (Create a Research Space) model. Based on the model, sixty Islamic research article introductions were analyzed in terms of the move structure and linguistic features that signal the use of the move. Findings show that most of the introductions contain all the moves prescribed by the model but the introductions that strictly follow the CARS Move structure is relatively small. This suggests that most of the introductions employ the rhetorical moves proposed by the CARS model, but deviate in terms of their organization.